Síntese e caracterização de complexos de Eu(III) com ligantes dicetona e diferentes fenantrolinas: aplicações antitumorais e interações com biomoléculas - Rocha, Josias da Silveira (Universidade Federal de São Carlos, 2025)
In this work, four Eu(III)-based complexes were synthesized and characterized using the dibenzoylmethane (DBM) ligand and various phenanthrolines, PH (4,7 diphenyl-1,10-phenanthroline); NON [1,2,5]oxadiazolo[3',4':5,6]pyrazino[2,3f][1,10]phenanthroline); CN (pyrazino[2,3-f][1,10]phenanthroline-2,3-dicarboni trile); and BrF (10-bromo-12-fluorodipyrido[3,2-a:2',3'-c]phenazine). Characterization was performed using techniques such as X-ray diffraction, elemental analysis (CHN), molar conductivity, magnetic susceptibility, and spectroscopy (UV-Vis, IR, 1D and 2D NMR, and fluorescence). The cytotoxicity of the ligands and complexes was evaluated against tumor cell lines, including lung (A549), prostate (DU-145), triple-negative breast cancer (MDA-MB-231), and cisplatin-resistant ovarian cancer (A2780cis), as well as a non-tumor lung cell line (MRC-5). The complexes demonstrated high inhibitory activity, often comparable to or exceeding that of the standard drug cisplatin. Among the tested compounds, the Eu(DBM)3PH and Eu(DBM)3BrF complexes stood out, displaying remarkable IC50 values of 0.850 µM and 3.57 µM, respectively, in the A2780cis cell line, with selectivity indices of 59.0 and 14.0, respectively. The mechanism of cell death in the A2780cis cell line was characterized as apoptotic, supported by morphological, clonogenic, and flow cytometry assays. In 3D cytotoxicity assays, the complexes demonstrated the ability to inhibit the growth of tumor spheroids. The Eu(DBM)3PH complex showed cytostatic activity, preventing cellular growth even at the lowest tested concentration (0.78 µM). Conversely, the Eu(DBM)3BrF complex exhibited dose- and time-dependent behavior, inhibiting cell growth at 6.25 µM after 96 hours. To investigate potential biomolecular targets, interaction studies were conducted with classical biomolecules such as DNA and Topoisomerase enzymes. Regarding DNA, the complexes predominantly interacted with the minor groove, with Eu(DBM)3PH achieving an 84.4% suppression of the Hoechst 33258 dye. In Topoisomerase IIα (TOPOIIα) inhibition assays, all complexes except Eu(DBM)3CN showed inhibitory activity at 20 µM. Moreover, the observed selectivity suggested that these complexes act as potential catalytic inhibitors of TOPOII, distinguishing themselves from enzyme poisons like etoposide. The complexes also demonstrated the ability to be biologically transported, showing intermediate to strong binding constants (Kb) in the range of 10⁵–10⁶ with human serum albumin (HSA). The obtained results in this thesis demonstrate the promising potential of Eu(III) complexes with diketone and phenanthroline ligands in the field of antitumor applications, highlighting their selectivity and efficacy in tumor cell models
Synthesis and characterization of Eu(III) complexes with Β-diketone ligands and different phenanthrolines: anti-Tumor applications and interactions with biomolecules
Keywords: Complexos de Eu(III); Agentes antitumorais; Interações com o DNA; Inibidores das enzimas Topoisomerases; Células 3D; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA